2004
DOI: 10.1038/sj.jp.7211216
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Inhaled Nitric Oxide on Pulmonary and Cardiac Function in Preterm Infants with Evolving Bronchopulmonary Dysplasia

Abstract: Low-dose iNO had no acute effects on lung function, cardiac function and oxygenation in evolving BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…These findings are consistent with data in a smaller preterm infant cohort 17 and data Figure 2 Repeated measurements of Rexp and Ckg during study gas administration. Repeated measurements of Rexp and Ckg were documented over a 2-week period after administration of study gas.…”
Section: Discussionsupporting
confidence: 81%
“…These findings are consistent with data in a smaller preterm infant cohort 17 and data Figure 2 Repeated measurements of Rexp and Ckg during study gas administration. Repeated measurements of Rexp and Ckg were documented over a 2-week period after administration of study gas.…”
Section: Discussionsupporting
confidence: 81%
“…Previous reports on the effects of iNO on lung mechanics gave contradictory results: Zayek et al 38 did not find any effect of iNO on Raw and TV in newborn lambs with PH; Zobel et al 6 demonstrated that iNO and inhaled PGI 2 do not change lung mechanics (included static compliance); Dupuy et al 39 demonstrated in guinea pig that iNO reduces pulmonary Raw; Potter et al 40 reported that iNO decreases Raw in newborn piglet; Athavale et al 41 found an improvement of lung compliance, but not of Raw in pre-term infants with evolving bronchopulmonary dysplasia; and finally, McCurnin et al 42 found that iNO increases Cdyn and decreases Raw in a baboon model of chronic lung disease. Moreover, Zobel et al 6 and Ragaller et al 43 excluded in animal models of lung injury any effects of PGI 2 on pulmonary mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have been published describing no significant effects of inhaled NO on respiratory system resistance in preterm infants [26,27], also affected by the respiratory syncytial virus [28]. Belik et al [29] showed that the content and the activity of the NOS competitor arginase in the rat lungs exhibit significant reduction with increasing age of the animals, from fetal life to newborns and adults.…”
Section: Discussionmentioning
confidence: 99%